Dicephalus Parapagus Conjoined Twins - Alfa Febrianda; Roza Sriyanti (Andalas Obstetrics And Gynecology Journal, 2024)
Background: Conjoined twins are monoamniotic monochorionic twins resulting from incomplete division of the embryonic disk and amniotic sac. This rare condition has an incidence of 1:33,000 to 1:165,000 pregnancies. Common types include thoracopagus and omphalopagus, with less common forms like thoracoomphalopagus, pyopagus, ischiopagus, and craniopagus. Parapagus, where twins are joined at the sides with a shared pelvis and organs, occurs in less than 0.5% of cases. Case: A 27-year-old patient presented to the Fetomaternal Clinic at RSUP M. Djamil Padang, referred from Hermina Hospital, with a diagnosis of G2P1A0H1 gravid preterm and suspected conjoined twins. Ultrasound at 5 months showed two heads and one body. Initial assessment noted a family history of twins and palpable round, firm masses. Laboratory tests, Fetomaternal ultrasound, MRI, and 3D CT Scan confirmed conjoined twins (dicephalus, parapagus, dibrachius). A cesarean section was planned. Discussion: Termination involves a multidisciplinary team to manage fetal anatomical abnormalities optimally. Emergency separation has a 70% mortality rate, higher than the 20% for elective procedures. Treatment depends on cardiovascular anatomy, with higher success if only the pericardium is divided. Cardiac anomalies' severity influences prognosis, survival, and separation feasibility. Survival rates depend on the degree of union and cardiac anomalies. In cases like dicephalus, the anatomical structure often makes it unlikely for both twins to survive separation.